1995
DOI: 10.1007/bf00189223
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of Taxus sp. cell cultures for production of taxol

Abstract: The addition of cell extracts and cultures filtrate of Pencillium minioluteum, Botrytis cinerea, Verticillium dahliae, and Gilocladium deliqucescens on the tenth day after transferring Taxus sp. (RO1-M28) cell suspensions into an induction medium, further improved the production of Taxol ® and total taxanes. Arachidonic acid (lmg/L) addition at the time of inoculation increased Taxol production by 150%. Oxidative stress induction and copper sulphate or sodium orthovanadate addition had no effect on Taxol produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 11 publications
1
34
1
2
Order By: Relevance
“…A concentration of 200 μM MeJA is recommended for improved the expression of these genes. Moreover, the timing of the application of MeJA is critical [48,49]. Our experimental results showed that treating S. grosvenorii fruit with MeJA at 30 DAF was better than at 10 or 20 DAF since six of the seven groups at 30 DAF showed a positive response to the stimulus (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…A concentration of 200 μM MeJA is recommended for improved the expression of these genes. Moreover, the timing of the application of MeJA is critical [48,49]. Our experimental results showed that treating S. grosvenorii fruit with MeJA at 30 DAF was better than at 10 or 20 DAF since six of the seven groups at 30 DAF showed a positive response to the stimulus (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…MeJA, SA, hydrogen peroxide and fungal extract have been reported to be capable of inducing the production of taxol (Stierle et al, 1993;Ciddi et al, 1995;Yukimune et al, 1996;Yu et al, 2001), but the mechanisms of these elicitors have not been completely understood. Especially, little has been reported on the relation between the above elicitors and the activity of cytochrome P450 monooxygenases or acetyltransferases.…”
Section: Introductionmentioning
confidence: 99%
“…The most promising longterm solution to taxol production seems to be from cell suspension cultures using modem biotechnology approaches (ShortIe and Minocha, 1999). Ciddi et al (1995) showed that the addition of several fungal cell extracts and culture filtrates resulted in an increase in the production of taxol in cell cultures of Taxus. Yukimune et al, (1996) were able to achieve increased production of taxol and its precursor baccatin III in taxus cell cultures by adding methyl jasmonate.…”
Section: Secondary Metabolite Productionmentioning
confidence: 98%